Integrative proteomic and physiological analyses reveal differential responses between high- and low-Cd-accumulating wheat under Cd stress - Wang, Qing; Li, Yuenan; Wang, Yixiu; Zhang, Mengjiao; Lv, Yonghui; Zhang, Haibo; Liu, Na; Cheng, Hongyan (Ecotoxicology and environmental safety, 2025)
Cadmium (Cd) pollution in farmland soil poses a potential threat to food safety and human health. To elucidate the physiological and molecular mechanisms of wheat response to Cd stress, proteomics and a weighted gene co-expression network analysis technology were used to investigate differences in the physiological and gene regulatory networks between high- and low-Cd-accumulating wheat. Physiological and biochemical analyses revealed the high-Cd-accumulating wheat ZM32 exhibited significantly higher Cd and sulfhydryl substance (non-protein thiol, glutathione, and phytochelatins) contents, as well as antioxidant enzyme (peroxidase, catalase, and superoxide dismutase) activity levels compared to the low-Cd-accumulating wheat JM22. However, the biomass exhibited an opposite trend. JM22’s lower Cd accumulation under low Cd stress may be attributed to the up-regulation of peroxidase in the phenylpropanoid biosynthesis pathway, as well as increased expression levels of DnaJ homolog subfamily B member 12, heat shock 70 kDa proteins 1/6/8, and chaperones in the endoplasmic reticulum (ER)-associated degradation system. These proteins play important roles in phenylpropanoid biosynthesis and protein processing in the ER. JM22’s lower Cd accumulation under high Cd stress may be attributed to the up-regulated of 2,4-dihydroxy-7-methoxy-1,4-benzoxazin-3-one in the benzoxazine biosynthesis, as well as increased expression levels of glutathione reductase, glutathione dehydrogenase/transferase, and glutathione peroxidase in the glutathione metabolism. Kyoto encyclopedia of genes and genomes (KEGG) and weighted gene co-expression network analysis showed that CFC21_021767, CFC21_050069, and CFC21_026131 encoded proteins associated with Cd resistance and low Cd accumulation ability. This study revealed the differences in gene regulatory networks between high- and low-Cd-accumulating wheat under Cd stress. The candidate proteins identified as being related to Cd accumulation can be utilized for genetic improvement of wheat through techniques, such as gene editing or transgenic approaches, with the aim of reducing the uptake and accumulation of Cd in wheat. [Display omitted] •Benzoxazinoid biosynthesis played a crucial role in JM22’s response to Cd stress.•Endoplasmic reticulum homeostasis contributed to enhancing JM22’s ability to resist Cd stress.•The proteins CFC21_021767, CFC21_050069, and CFC21_026131 played roles in reducing Cd toxicity and decreasing Cd accumulation in JM22.